1998
DOI: 10.1038/sj.bjp.0702229
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of digoxin on testosterone secretion through mechanisms involving decreases of cyclic AMP production and cytochrome P450scc activity in rat testicular interstitial cells

Abstract: 1 In vivo and in vitro experiments were performed to examine inhibitory e ects of digoxin on testosterone secretion and to determine possible underlying mechanisms. 2 A single intravenous injection of digoxin (1 mg kg 71 ) decreased the basal and human chorionic gonadotropin (hCG)-stimulated plasma testosterone concentrations in adult male rats. 3 Digoxin (10 77 ± 10 74 M) decreased the basal and hCG-stimulated release of testosterone from rat testicular interstitial cells in vitro. 4 Digoxin (10 77 ± 10 74 M)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 23 publications
2
28
0
Order By: Relevance
“…The water bath chamber was kept saturated with 95% O 2 and 5% CO 2 . Each preparation contained approximately 20% Leydig cells [Lin et al, 1998]. …”
Section: Preparation Of Ticsmentioning
confidence: 99%
“…The water bath chamber was kept saturated with 95% O 2 and 5% CO 2 . Each preparation contained approximately 20% Leydig cells [Lin et al, 1998]. …”
Section: Preparation Of Ticsmentioning
confidence: 99%
“…The water bath chamber was kept saturated with 95% O 2 and 5% CO 2 . Each preparation was found to contain approximately 20% Leydig cells [Lin et al, 1998]. …”
Section: Preparation Of Rat Testicular Interstitial Cells (Tics)mentioning
confidence: 99%
“…This inhibitory effect of bufalin is associated in part with a decrease of testicular cAMP accumulation and luteinizing hormone (LH) response to gonadotropin-releasing hormone (GnRH) . Third, we recently showed that digoxin inhibited testosterone production in rat testicular interstitial cells through attenuation of the activities of adenylyl cyclase and cytochrome P450scc [Lin et al, 1998]. In addition, digitoxin was shown to interfere the binding of dihydrotestosterone on rat ventral prostate [Pita et al, 1975] and estrogen on human uteri [Rifka et al, 1977].…”
mentioning
confidence: 98%